2018
DOI: 10.17645/mac.v6i2.1317
|View full text |Cite
|
Sign up to set email alerts
|

Running Head: Video Game Nostalgia and Retro Gaming

Abstract: This article conceptually integrates research on the experience of nostalgia—defined as a predominantly positive, social, and past-oriented emotion—into the fold of video game research. We emphasize the role of nostalgia as an explanation for contemporary retro gaming trends, and suggest that nostalgia towards gaming events is a necessary area of research. To those ends, we broadly review existing literature on nostalgia before specifically focusing on media-induced nostalgia, and demonstrate how theoretical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 36 publications
1
21
0
3
Order By: Relevance
“…Games are one of the most frequently encountered forms of entertainment in modern society. Adults today spend more time playing video games than previous generations have (Williams et al, 2008), and this is likely due to the fact that most adults grew up playing video games (Wulf et al, 2018).…”
mentioning
confidence: 99%
“…Games are one of the most frequently encountered forms of entertainment in modern society. Adults today spend more time playing video games than previous generations have (Williams et al, 2008), and this is likely due to the fact that most adults grew up playing video games (Wulf et al, 2018).…”
mentioning
confidence: 99%
“…La prégnance de la nostalgie dans ces pratiques peut être considérée comme un facteur expliquant le succès du retrogaming selon Wulf et al (2018), ouvrant notamment des perspectives de recherche sur le rôle encore méconnu du matériel dans ce cadre. La nostalgie désigne ici un « désir de retourner à une époque passée », pouvant « s'articuler à d'autres temporalités » (Niemeyer 2016), pouvant être associé à des activités créatives, et relié à la notion d'identité et à l'appartenance à une communauté (Niemeyer 2014 ;.…”
unclassified
“…La nostalgie désigne ici un « désir de retourner à une époque passée », pouvant « s'articuler à d'autres temporalités » (Niemeyer 2016), pouvant être associé à des activités créatives, et relié à la notion d'identité et à l'appartenance à une communauté (Niemeyer 2014 ;. Nous interrogerons ici la place de la nostalgie dans les activités de joueurs en tant qu'« émotion consciente » et complexe, en la considérant comme « principalement positive et fondamentalement sociale » (Sedikides et al, 2015, p. 190 ;Wulf et al, 2018).…”
unclassified
“…These authors also describe how nostalgia can be a source of meaning in life, which is also conceptually connected to henosis. One way that nostalgia can be elicited is by external experiences that remind people of pleasant and meaningful experiences from the past (Sedikides et al, 2015), and this has been shown to be a motivating reason why some video games are played (Wulf, Bowman, Rieger, Velez, & Breuer, 2018). Given that henotic experiences tap into the very foundational assumptions people have about their world, it seems likely that reflecting back on these experiences should result in nostalgia, which makes this good measure of predictive validity.…”
Section: Transitioning From Themes To Itemsmentioning
confidence: 99%
“…Meaningfulness-at least, as the term is used colloquially-can conceivably refer to numerous types of experiences that are subjectively described as such. It is worth noting that meaningful experiences in games often seem to involve playing and experiencing games with other people (De Schutter & Vanden Abeele, 2010;Oliver et al, 2016), and that games have been socially oriented (Bowman, 2018), and thus potentially meaningful, long before developers began focusing on engendering insight, poignancy and contemplation. Unsurprisingly, many scholars have rightly pointed out that the notion of meaningfulness as a media experience is quite multifaceted (Wirth, Hofer, & Schramm, 2012), and that further research and theorizing is needed to account for its manifestations and underlying psychological components.…”
Section: Introductionmentioning
confidence: 99%